An Approximation Theorist’s view on solving operator equations—With special attention to Trefftz, MFS, MPS, and DRM methods - Schaback, Robert (Computers & mathematics with applications (1987), 2021)
When an Approximation Theorist looks at well-posed PDE problems or operator equations, and standard solution algorithms like Finite Elements, Rayleigh–Ritz or Trefftz techniques, methods of fundamental or particular solutions and their combinations, they boil down to approximation problems and stability issues. These two can be handled by Approximation Theory, and this paper shows how, with special applications to the aforementioned algorithms. The intention is that the Approximation Theorist’s viewpoint is helpful for readers who are somewhat away from that subject.